Cherenkov radiation of a laser pulse in ion dielectrics - Balakirev, V.A.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2019)
The process of excitation of Cherenkov electromagnetic radiation by a laser pulse in ion dielectric waveguide is investigated. Nonlinear electric polarization in isotropic ion dielectric medium and, accordingly, polarization charges and currents induced by a ponderomotive force of a laser pulse are determined. Frequency spectra of the excited wakefields in the infrared and microwave frequency ranges are obtained. The spatiotemporal structure of the wakefield in ion dielectric waveguide is obtained and studied. It is shown that the excited field consists of a potential polarization electric field, as well as a set of eigen electromagnetic waves of ion dielectric waveguide.